How Brazil’s President turned the country into a global epicenter of COVID-19 - Fearnside, Philip Martin; Tupinambás, Unaí; Vassão, Ruth Camargo; Leão, Jeremias; Almeida, Alexandre C.L.; Steinmetz, Wilhelm Alexander; Duczmal, Luiz Henrique; Ferrante, Lucas (Journal of Public Health Policy, 2021)
In this manuscript, we point out that the federal government headed by President Bolsonaro has pursued a political agenda that contributed to the spread of COVID-19, transforming the country into a major repository for SARS-CoV-2 and its variants, thus representing a risk for worldwide containment efforts. Furthermore his actions are also weakening democratic institutions, which could counter his political agenda, effectively facilitating the spread of COVID-19. Thus, the perpetuation of the COVID-19 pandemic in Brazil is due to human behaviour factors, especially high-level public decision makers. © 2021, The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: Bolsonaro; Coronavirus; Epidemiology